May we borrow your language? : how english has stolen, snaffled, purloined, pilfered, appropriated and looted words from all four corners of the world - Gooden Philip (c, 2016)
The English language that is spoken by one billion people around the world is a linguistic mongrel, its vocabulary a diverse mix resulting from centuries of borrowing from other tongues. From the Celtic languages of pre-Roman Britain to Norman French; from the Vikings' Old Scandinavian to Persian, Arawak, Cantonese, Hawaiian, Hebrew, Inuit and Erdu - amongst a host of others - we have enriched our modern language with such words as tulip, slogan, doolally, avocado, moccasin, ketchup and ukulele. May We Borrow Your Language? explores the intriguing and unfamiliar stories behind scores of familiar words that the English language has filched from abroad; in so doing, it also sheds fascinating light on the wider history of the development of the English we speak today. Full of etymological nuggets to intrigue and delight the reader, this is a gift book for word buffs to cherish - as cerebrally stimulating as it is more-ishly entertaining.
Keywords: COMPARATIVE LINGUISTICS; ENGLISH LANGUAGE -- ETYMOLOGY; ENGLISH LANGUAGE -- SEMANTICS